2020
DOI: 10.1021/jacs.0c07482
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Nonporous Adaptive Pillar[4]arene[1]quinone Crystals into Fluorescent Crystals via Multi-Step Solid–Vapor Postsynthetic Modification for Fluorescence Turn-on Sensing of Ethylenediamine

Abstract: Organic solid-state fluorescent crystals have received extensive attention owing to their remarkable and promising optoelectronic applications in many fields. Current methods to obtain organic fluorescent crystals usually involve two steps: (1) solution phase organic synthesis and (2) crystallization of target fluorescent compounds. Direct transformation from nonfluorescent organic crystals to fluorescent organic crystals by postsynthetic modification (PSM) might be a potential alternative to the traditional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 82 publications
0
51
0
Order By: Relevance
“…Despite the CD signals at 310 nm, new Cotton effects appeared in the region of 300–400 nm of 1a and 2a , which could be ascribed to the transition of 2,5-bis(alkyl/arylamino)-1,4-benzoquinones ( Martini and Nachod, 1951 ; Li et al, 2020 ). In addition, strong Cotton effects in CT transition in the wavelength region of 400–700 nm were observed ( Wang H. J. et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the CD signals at 310 nm, new Cotton effects appeared in the region of 300–400 nm of 1a and 2a , which could be ascribed to the transition of 2,5-bis(alkyl/arylamino)-1,4-benzoquinones ( Martini and Nachod, 1951 ; Li et al, 2020 ). In addition, strong Cotton effects in CT transition in the wavelength region of 400–700 nm were observed ( Wang H. J. et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of chiral pillar[5]arenes without the complicated chiral resolution processes should be more convenient and valuable for studying supramolecular chirality switching. It has been reported that 1,4-benzoquinone undergoes the Michael addition reaction with aliphatic or aromatic amines to selectively afford 2,5-bis(alkyl/arylamino)-1,4-benzoquinones ( Almeida Barbosa et al, 2010 ; Strutt et al, 2014a ; Li et al, 2018 ; Kiruthika et al, 2020 ; Li et al, 2020 ). In this work, we report the synthesis of several new chiral pillar[4]arene[1]quinone derivatives and their unique chiroptical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new macrocyclic hosts has enriched the scope of vapochromic crystals in recent years. [56][57][58][59][60] The special feature of supramolecular vapochromic crystals is that the vapor-responsive detection can be achieved by changing the host-guest interactions. Based on the presence or absence of ICT interaction between P5 and G1 and from weak to strong ICT interaction between P5 and G10, obvious acid/base-responsive switchable processes with color changes visible to the naked eye could be achieved in solution.…”
Section: Acid/base-responsive Vapochromic Properties In the Crystalli...mentioning
confidence: 99%
“…They are similar to calixarenes, but the linkages between the phenols lead to pillar-like, highly symmetrical structures (Behera et al, 2020). Pillararenes have been used in a variety of supramolecular applications, including for the binding and removal of organic toxicants from contaminated aqueous environments (Fernando et al, 2019); as components of solidstate crystalline structures (Li et al, 2020a); and as nanochannels for biomimetic research (Sun et al, 2020). Like the macrocycle classes previously discussed, pillararenes rely primarily on hydrophobic association to bind small-molecule hydrophobic guests (Shen et al, 2018), with particular examples reported using electrostatic interactions (Liu et al, 2019b) and/or intermolecular hydrogen bonding (Han et al, 2020a) as cooccurring mechanisms.…”
Section: Pillararenesmentioning
confidence: 99%